Maintaining wellbeing in remote work: a digital ethnography into resources, boundaries, and time - Yalçınyiǧit, Serap (Frontiers in Psychology, 2026)
AimThis study examines remote work as a form of virtual mobility and its implications for employees' subjective wellbeing (SWB). Using the complementary perspectives of Conservation of Resources (COR) and boundary theory, it presents a theoretical framework that explains how resource dynamics, boundary permeability, and time perceptions influence wellbeing in remote work.MethodsThe study employs a digital ethnographic design based on 11 semi-structured interviews. These are complemented by field notes and an experiential elicitation task. The data were analyzed using reflexive thematic analysis, supported by computational techniques such as similarity measures, co-occurrence networks, and visualization tools implemented in R.ResultsThe findings identify three overarching themes: temporal experiences, in which acceleration, stagnation and fluctuating emotional rhythms that disrupted affective wellbeing; blurred boundaries, in which work-home permeability, erosion of collegial ties, and selective connections that reshape SWB; and coping strategies, which included boundary setting practices, job crafting, rituals, and recovery. The experimental task revealed a systematic bias toward underestimating time, consistent with participants' narratives of drift in monotonous work contexts.ConclusionThe study advances research into mobility and wellbeing theoretically by framing virtual mobility and multidimensional SWB, methodologically by showcasing the value of digital ethnography for capturing lived experiences, and practically by underlining the importance of organizational support and policies.